Adoption of adaptation protocols and feed additives to improve performance of feedlot cattle - Silvestre, Antonio M. [UNESP]; Souza, Johnny M. [UNESP]; Millen, Danilo D. [UNESP] (Taylor & Francis, 2023)
The evolution of ruminants was largely influenced by the symbiotic relationship between ruminal microbiota and the host. Within the rumen, these microorganisms degrade feedstuffs to produce organic acids and synthesize microbial protein, as energy and protein source for ruminants, respectively. This process is accelerated when these animals are transferred to feedlot diets. This review brings the most current studies that reported the most used nutritional managements in this transition process, in order to avoid metabolic disturbances, in which rumen development is a fundamental point. Also, this review brings the main biomolecules used as feed additive, which can in the help control of fermentation processes in order to minimize energetically inefficient processes within the rumen, as well as losses by excretion to the environment, which are widely questioned by be environmental pollutants. Furthermore, the main results of research on animal performance in response to these additives are reported, supplemented alone or associated with different feed additives when used on diets with high grain contents, as well as evaluating the potential of additives as antibiotics alternatives, a fact that has been discussed and is worrying since the use of ionophores or non-ionophores antibiotics represent practically the totality of feedlot diets.
Keywords: Energy concentration; feedlot; fermentation; metabolism; performance; ruminal microbe